Research on the System Architecture of EV Motor Control Unit Based on Functional Safety - WU Lixun; CHEN Jianming; CHEN Lei; ZHENG Hanfeng (Kongzhi Yu Xinxi Jishu)
This paper presented the basic methods of hazard analysis and risk assessment which based on the functional safety related standards, and then the safety goal and ASIL of EV motor control unit have been derived according to HARA. The implementation method of function monitoring level was proposed through the analysis of EGAS architecture and verified by Matlab simulation analysis and Dyno test, and then the design method of the realization of system functional safety architecture for different microprocessor structure was expanded. The results show that the system safety architecture of dual chip microprocessors has significant advantages in the realization of safety goal and the standardized product development.